2017
DOI: 10.1021/acs.jproteome.7b00468
|View full text |Cite
|
Sign up to set email alerts
|

A Serum Small Molecule Biosignature of Radiation Exposure from Total Body Irradiated Patients

Abstract: The potential for radiological accidents and nuclear terrorism has increased the need for the development of new rapid biodosimetry methods. In addition, in a clinical setting the issue of an individual’s radiosensitivity should be taken into consideration during radiotherapy. We utilized metabolomics and lipidomics to investigate changes of metabolites in serum samples following exposure to total body ionizing radiation in humans. Serum was collected prior to irradiation, at 3–8 h after a single dose of 1.25–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…It has been reported that levels of AA and eicosanoids derived from AA increase in the serum of mice at 24 h following irradiation (Laiakis et al, ). Moreover, a striking increase in free fatty acids including AA, Ole and pro‐inflammatory eicosanoids was observed in total body‐irradiated patients (Laiakis et al, ). These eicosanoids by the cytochrome P‐450 enzymatic pathway are the primary metabolites from AA in the brain (Roman, ) and play important roles in renal and cardiovascular functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that levels of AA and eicosanoids derived from AA increase in the serum of mice at 24 h following irradiation (Laiakis et al, ). Moreover, a striking increase in free fatty acids including AA, Ole and pro‐inflammatory eicosanoids was observed in total body‐irradiated patients (Laiakis et al, ). These eicosanoids by the cytochrome P‐450 enzymatic pathway are the primary metabolites from AA in the brain (Roman, ) and play important roles in renal and cardiovascular functions.…”
Section: Resultsmentioning
confidence: 99%
“…As an environmental stimulus, radiation exposure inevitably causes perturbations of metabolic response. Multiple previous studies based on metabolomics have been applied for assessing ionizing radiation exposure from rodents, nonhuman primates and total body‐irradiated patients (Coy et al, ; Laiakis et al, ; Pannkuk, Laiakis, Fornace, Fatanmi, & Singh, ). Because of the easy sample collection and less invasive nature, biofluids (urine, plasma and serum) are the main sources of biomarkers for radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, blood metabolomic markers may be able to distinguish the type of radiation one is exposed to, as was found when mice were exposed to X-ray vs. neutron radiation [36]; or determine specific organ injury, as Jones et al found when studying small intestine tissue metabolites compared to plasma metabolites of mice exposed to TBI [114]. Importantly, some metabolite signatures, including increases in polyunsaturated fatty acid-containing lipids, have been consistently found across mice [115,116], NHPs [26,117], and humans [118], over a range of radiation doses. Not only is blood a useful biosample to assess acute radiation response, but can also be used to predict delayed effects of acute radiation exposure (DEARE).…”
Section: Bloodmentioning
confidence: 91%
“…Thus, it is extremely important to collect samples longitudinally to track these functional metabolomic changes, in order to determine progression of injury and timepoints with greatest diagnostic and prognostic accuracy [123]. Temporal changes in metabolomic biomarkers can also vary depending on sex [22,118,126,154], as discussed earlier. Additionally, temporal metabolomic changes and diagnostic/prognostic accuracy of metabolomic markers may vary depending on the sample type [127,140], which is also a factor to consider when designing biomarker discovery and validation studies.…”
Section: Other Types Of Biofluid (Sebum Sputum Breath Tears)mentioning
confidence: 99%
“…Hücreyi Sorumlu Yazar / Corresponding Author: Yaşar Aysun MANİSALIGİL, aysun.manisaligil@deu.edu.tr Geliş Tarihi / Received: 05.09.2018 Kabul Tarihi / Accepted: 25.10.2018 Bu çalışma, II. Uluslararası Katılımlı Radyasyondan Korunma Kongresi'nde (23)(24)(25) Kasım 2017, Ankara) sözlü bildiri olarak sunulmuştur.…”
Section: Introductionunclassified